A pedagogy of abundance - Weller, Martin (Revista Española de Pedagogía, 2016)
The digitalisation of content combined with a global network for delivery and an open system for sharing has seen radical changes in many industries. The economic model which has underpinned many content based industries has been based on an assumption of scarcity. With a digital, open, networked approach we are witnessing a shift to abundance of content, and subsequently new economic models are being developed which have this as an assumption. In this article the role of scarcity in developing higher education practice and pedagogy is explored. The shift to abundant content has as profound implications for education as it has for content industries. The possible contenders for a ‘pedagogy of abundance’ are examined and the necessary requirements for such a pedagogy outlined.
Keywords: pedagogy, e-learning; higher education; Revista Española de Pedagogía; web 2.0; digital economy